Feasibility of high-flow nasal cannula implementation for children with acute lower respiratory tract disease in rural Kenya. (3rd July 2019) - Von Saint André-Von Arnim, Amélie O.; Okeyo, Bob; Cook, Nathan; Steere, Mardi; Roberts, Joan; Howard, Christopher R. A.; Stanberry, Larissa I.; John-Stewart, Grace C.; Shirk, Arianna
ABSTRACT: Background : High-flow nasal cannula (HFNC) is a well-established respiratory support device in high-income countries, but to our knowledge, its use in sub-Saharan Africa has not been reported. This feasability study describes the implementation process of HFNC in rural Kenya. Methods : HFNC was implemented in intensive care and high dependency units at Kijabe Hospital, Kenya for children with acute lower respiratory disease. Rate of intubation was compared with historical controls and challenges of implementation described. Results : Fifteen patients received HFNC between January and November 2016, and compared to 25 historical control patients. Both groups had many comorbidities, and control patients were significantly younger. There were no significant differences in clinical outcome between the groups: 5 (33%) HFNC vs 12 (48%) controls required intubation; 10 (67%) HFNC vs 22 (88%) controls survived to discharge; and the HFNC required 3 vs the controls' 4 days on respiratory support. The greatest technical issues encountered were large pressure differences between air from a wall outlet (wall air) and oxygen and an inability to automatically refill humidifier water chambers. Conclusion : HFNC in limited-resource settings is feasible but there were technical challenges and concern about the increased workload. The small sample size, heterogeneous population, availability of oxygen and blending of wall air at the study site limit inferences for other sites in low- and middle-income countries. Abbreviations : ALRI, acute lower respiratory infection; CPAP, continuous positive airway pressure; ETAT, emergency triage, assessment and treatment; HDU, high dependency unit; HFNC, high-flow nasal cannula; HIC, high-income country; HR, heart rate; ICU, intensive care unit; LMIC, low- and middle-income countries; PSI, pounds per square inch; RR, respiratory rate; mRISC, modified Respiratory Index of Severity in Children.